2022
DOI: 10.1128/spectrum.02262-21
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Virus-Like Particle Neutralizing Capacity in Blood Donors Depends on Serological Profile and Donor-Declared SARS-CoV-2 Vaccination History

Abstract: In the first 3 months of 2021 as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination was in the initial stages of a mass rollout, Canadian blood donors had various levels of humoral protection against wild-type and variant of concern (VOC) SARS-CoV-2. Very few Canadians would have received a second dose of a SARS-CoV-2 vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…There were also recommendations against the use of CCP for treating COVID-19 in “hospitalized patients without impaired humoral immunity” ( 1 ). Our group at Canadian Blood Services previously was focused on supporting CCP studies in Canada ( 2 5 ), and this led us to initiate a “correlates of immunity” project, which had the stated goal of understanding changes in anti-severe acute respiratory syndrome coronavirus 2 (anti-SARS-CoV-2) neutralizing capacity as the COVD-19 pandemic advanced and identifying methods to identify and characterize high-titer donor plasma ( 2 , 3 , 6 , 7 ). During this preliminary work, we validated 50% plaque reduction/neutralization titer (PRNT 50 ) assays using binding antibody, competitive binding assays, and virus-like particle (VLP) assays for wild-type SARS-CoV-2 ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also recommendations against the use of CCP for treating COVID-19 in “hospitalized patients without impaired humoral immunity” ( 1 ). Our group at Canadian Blood Services previously was focused on supporting CCP studies in Canada ( 2 5 ), and this led us to initiate a “correlates of immunity” project, which had the stated goal of understanding changes in anti-severe acute respiratory syndrome coronavirus 2 (anti-SARS-CoV-2) neutralizing capacity as the COVD-19 pandemic advanced and identifying methods to identify and characterize high-titer donor plasma ( 2 , 3 , 6 , 7 ). During this preliminary work, we validated 50% plaque reduction/neutralization titer (PRNT 50 ) assays using binding antibody, competitive binding assays, and virus-like particle (VLP) assays for wild-type SARS-CoV-2 ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the labor-intensive nature of PRNT 50 testing, we also noted a requirement for a laboratory-based rapid screening assay to identify high-titer CCP and to decrease overall tests costs per unit of qualified CCP. We also later determined that the neutralizing capacity of donor plasma could vary between wild-type and emerging variants of concern (VOCs) ( 7 ). The rationale to use CCP in early stage COVID-19 is further supported in the study that SARS-CoV-2 virus can only be cultured from early stage COVID-19 patients ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Assays that bridge between qualitative binding and quantitative neutralization are important, and this study focused on the qualitative binding element of immunity. In our previous studies, we have shown a difference in detection of binding versus neutralizing anti-SARS-CoV-2 antibodies in specimens from the same cohort of blood donors in our Correlates of Immunity project ( 9 , 10 ). Other work has shown that not all binding antibodies correlate to neutralization but that IgG against RBD (and to a lesser extent, S) can act as an indicator of neutralization ( 2 , 42 ).…”
Section: Discussionmentioning
confidence: 91%
“…The identification of waning neutralizing antibody responses in blood donors ( 1 ) led to the development of a further “Correlates of Immunity” project, which had the stated goal of understanding changes in anti-SARS-CoV-2-neutralizing capacity as the COVID-19 pandemic advanced. As part of this Correlates of Immunity project, our group was able to sample 1,500 retention specimens a month from Canadian blood donors using a repeated cross-sectional design with random cross-sectional sampling of all available retention samples for a 12-month period from April 2020 until March 2021 ( 6 10 ). During this process, we used a variety of assays that have been widely used by our and other groups to assess SARS-CoV-2 seroprevalence in Canada.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation